Management Practices and Economic Contribution of Eucalypts Woodlots to the Rural Household Livelihoods: The Case of Cheha District, Southern Ethiopia - Kebede Gizachew Gebremedhin; Efrem Garedew Negash (CV. Literasi Indonesia, 2023)
In Ethiopia rural households growing Eucalypts at farm level in the form of woodlot become popular and Eucalyptus woodlot products play a significant role in household economy in particular and economic development of the nation in general. This study was conducted in Cheha districts in the Guraghe zone to assess the farmers’ management practices and analyze the socioeconomic contribution of Eucalypts woodlot to the livelihood of the rural households in the area. Economic data was collected by employing a formal survey using a structured questionnaire. Woodlot inventory was conducted on farmers’ eucalyptus woodlots to identify the existing trees' frequency distribution by diameter classes that indicated economic value. The latest version of Stata, version 13, SAS version 9.1, sigma plot version 12, and Microsoft Excel were used to analyze the data. The result of the study revealed that most of the sampled farmers in the study area had Eucalypts woodlot, targeting either to earn more income or to increase the productivity of the land which has denied growing cereal crops and pastures. Most of the farmers considered Eucalypts as one of the major sources of income and risk aversion. Excluding household consumption, the aggregate cash income contribution of Eucalypts woodlot products to rural households was more than 34% for midland and 37% for highland agro-ecologies. Further studies are needed on the management aspect of Eucalypts woodlots for the productivity of allocated land.